82-x+3=(2+4x)

Simple and best practice solution for 82-x+3=(2+4x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 82-x+3=(2+4x) equation:



82-x+3=(2+4x)
We move all terms to the left:
82-x+3-((2+4x))=0
We add all the numbers together, and all the variables
-x-((4x+2))+82+3=0
We add all the numbers together, and all the variables
-1x-((4x+2))+85=0
We calculate terms in parentheses: -((4x+2)), so:
(4x+2)
We get rid of parentheses
4x+2
Back to the equation:
-(4x+2)
We get rid of parentheses
-1x-4x-2+85=0
We add all the numbers together, and all the variables
-5x+83=0
We move all terms containing x to the left, all other terms to the right
-5x=-83
x=-83/-5
x=16+3/5

See similar equations:

| c4−2=2 | | (5+3x)x12=72 | | -3a-30+10a=5 | | x.0.25(4-8x)=7-(3x+5) | | 1.6(s-2)=8 | | 20/x=30 | | 3y+5=100 | | -3/r=3 | | ∠B=x93∘ | | x=74=23 | | 2n=-2-3(-4) | | 8.3x-1.4=15.2 | | 13(3j+6)= | | 2(x-16)=8(x-1) | | 2x-2+3x=73 | | 2x+6=-3x+9 | | x+135=120 | | 23x-12=180 | | 1=f4−2 | | 9w–7=-7 | | 54+x=60 | | 6x+48=6(x+ | | (12+5)×16÷2+48=x | | 9=2q−5 | | 7+1(b+-4)=(7+b)+-4 | | x=3.1/3x2+2 | | 28+4b=1/2 | | 4v+1=7v-5 | | 5x+8+7x-16=180 | | 15x+2x+–12x=–15 | | 6x+4=2x+68 | | 14u-7u-3u=12 |

Equations solver categories